2018
DOI: 10.1038/s41416-018-0090-1
|View full text |Cite
|
Sign up to set email alerts
|

Variation in treatment and survival of older patients with non-metastatic breast cancer in five European countries: a population-based cohort study from the EURECCA Breast Cancer Group

Abstract: Background Older patients are poorly represented in breast cancer research and guidelines do not provide evidence based recommendations for this specific group. We compared treatment strategies and survival outcomes between European countries and assessed whether variance in treatment patterns may be associated with variation in survival. Methods Population-based study including patients aged ≥ 70 with non-metastatic BC from cancer registries from the Netherlands, Belgi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
54
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 27 publications
7
54
2
Order By: Relevance
“…Only 101 women (4.1%) with stage I-III cancer, and 7 women (3.8%) with metastatic disease received chemotherapy. Elderly women in the current cohort were significantly less likely to receive chemotherapy as age and level of co-morbidity increased, which is in accordance with other research [4,11,12,16,23,[35][36][37][38][39]. A number of valid reasons do preclude the provision of chemotherapy in older women; chemotherapy use typically decreases with increasing level of co-morbidity [38,40], physicians may prefer not to administer it due to toxicity [9,11,14] and the potential impact on fitness [10,18,41].…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Only 101 women (4.1%) with stage I-III cancer, and 7 women (3.8%) with metastatic disease received chemotherapy. Elderly women in the current cohort were significantly less likely to receive chemotherapy as age and level of co-morbidity increased, which is in accordance with other research [4,11,12,16,23,[35][36][37][38][39]. A number of valid reasons do preclude the provision of chemotherapy in older women; chemotherapy use typically decreases with increasing level of co-morbidity [38,40], physicians may prefer not to administer it due to toxicity [9,11,14] and the potential impact on fitness [10,18,41].…”
Section: Discussionsupporting
confidence: 87%
“…However, radiotherapy use declined with increasing age and level of co-morbidity. Declining rates of radiotherapy with advancing age have also been reported in a variety of countries [4,11,16,23,[35][36][37].…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Also, treatment strategies of early breast cancer vary markedly both nationally and internationally. In two recent studies, elderly patient populations from European countries were compared [7,8]. These studies found a great variance in treatment: in the British population 47.8% of patients received surgery in comparison to 90.5% in the Dutch population [7].…”
Section: Introductionmentioning
confidence: 99%